Iliopsoas Release: A Systematic Review of Clinical Efficacy and Associated Complications. Issue 6 (6th November 2021) - Longstaffe, Robert; Hendrikx, Shawn; Naudie, Douglas; Willits, Kevin; Degen, Ryan M.
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objective: To perform a systematic review of the findings of iliopsoas release as it relates to resolution of snapping, improvement of groin pain, and associated complications. Design: Systematic review. Data Sources: Four electronic databases PubMed/MEDLINE, EMBASE, CINAHL, and Web of Science were searched, identifying all literature pertaining to surgical treatment of a snapping hip/coxa saltans, iliopsoas impingement, or iliopsoas tendinitis. A total of 818 studies were identified. Two reviewers independently screened the titles, abstracts, and full-text articles for eligibility. Eligibility Criteria: All studies published in English that reported on iliopsoas release for snapping hip/coxa saltans, iliopsoas impingement, or iliopsoas tendinitis reporting outcomes or associated complications were eligible. Results: A total of 48 articles were included in this review. Three surgical indications were identified for iliopsoas release, internal snapping hip, labral tear secondary to iliopsoas impingement, and iliopsoas tendinopathy after total hip arthroplasty. Arthroscopic techniques seemed to be superior to open techniques with regards to reoccurrence of snapping (5.1% vs 21.7%) and groin pain relief (89.1% vs 85.6%) with fewer complications (4.2% vs 21.1%) overall. Conclusions: Both open and arthroscopic iliopsoas releases have been shown to be successful treatment options regardless of the surgical indications identified in this review. Arthroscopic release demonstrated a decreased failure rate, fewer complications, and improved outcomes when compared with open procedures.